Increased Acid Exposure on Pretransplant Impedance-pH Testing Is Associated With Chronic Rejection After Lung Transplantation. Issue 6 (July 2020) - Lo, Wai-Kit; Moniodis, Anna; Goldberg, Hilary J.; Feldman, Natan; Chan, Walter W.
Abstract : Goal: The goal of this study was to assess the relationship between pretransplant measures of reflux and longer-term outcomes of chronic allograft rejection in lung transplant recipients. Background: Bronchiolitis obliterans syndrome (BOS) is a primary measure of morbidity and mortality following lung transplantation, and a manifestation of chronic lung allograft dysfunction (CLAD). Acid reflux has been associated with early allograft injury through a proposed mechanism of aspiration and activation of the inflammatory cascade, but its association with chronic rejection is unclear. Study: This was a retrospective cohort study of lung transplant recipients undergoing impedance-pH testing off proton pump inhibitor from 2007 to 2016. Patients with pretransplant antireflux surgery were excluded. Time-to-event analysis using the Cox proportional hazards model was applied to assess the relationship between pretransplant reflux measures and the development of BOS, defined histologically and clinically. A secondary analysis was completed using CLAD as the outcome variable. Results: Fifty-one subjects (59% men, mean age: 56, mean follow-up: 2.2 y) met inclusion criteria for the study. The BOS endpoint was reached in 13 subjects (28%). In time-to-event analyses, BOS was associated with increased acid exposure, defined as >4.2% of time with pH<4 [hazard ratio (HR): 4.18; 95% confidence interval (CI): 1.31-13.4; P =0.01], and elevated DeMeester score >14.7 (HR: 3.08; 95% CI: 1.02-9.26; P =0.04), with confirmation from Kaplan-Meier analyses. The secondary analysis demonstrated a similar association between increased acid exposure and CLAD (HR: 3.28; 95% CI: 1.09-9.88; P =0.03), which persisted on multivariate models. Conclusion: Increased acid exposure on pretransplant reflux testing was associated with the development of BOS and CLAD, both measures of chronic allograft rejection, after lung transplantation, and may provide clinically relevant information to improve lung allograft survival through aggressive reflux management.